DNA Binding and Anticancer Properties of New Pd(II)-Phosphorus Schiff Base Metal Complexes - Burcu Saygıdeğer Demir; Simay İnce; Mustafa Kemal Yilmaz; Aycan Sezan; Ezgi Derinöz; Tugba Taskin-Tok; Yasemin Saygideger (MDPI AG, 2022)
DNA has become the target of metal complexes in cancer drug discovery. Due to the side effects of widely known cisplatin and its derivative compounds, alternative metal-based drug discovery studies are still ongoing. In this study, the DNA-binding ability of Pd(II) and Pt(II) complexes of four phosphorus Schiff base ligands and four hydrazonoic-phosphines are investigated by using in silico analyses. Phosphorus Schiff base-Pd(II) complexes encoded as B1 and B2 with the best DNA-binding potential are synthesized and characterized. The DNA-binding potentials of these two new Pd(II) complexes are also investigated experimentally, and their antitumor properties are demonstrated in vitro in A549, MCF7, HuH7, and HCT116 cancer cells. The mechanisms of these metal complexes that kill the cells mentioned above in different activities are elucidated by flow cytometry apoptosis analysis and colony formation analysis The in silico binding energies of these two new palladium complexes ΔG (B1): −4.51 and ΔG (B2): −6.04 kcal/mol, and their experimental DNA-binding constants were found as Kb (B1): 4.24 × 105, Kb (B2): 4.98 × 105). The new complexes, which show different antitumor effects in different cells, are the least effective in HuH7 liver cells, while they showed the best antitumor properties in HCT116 colon cancer cells.